Efektivitas Rehabilitasi Pecandu Narkotika (Studi di Loka Rehabilitasi Badan Narkotika Nasional Batam) - Lysa Angrayni; Yusliati (Faculty of Law Universitas Lancang Kuning, 2018)
The purpose of this study: First, to explain the effectiveness of rehabilitation of narcotics addicts and their effects on crime rates in Indonesia at the BNN Rehabilitation Loka Batam. Second, to explain the obstacles faced in the process of rehabilitation of narcotics addicts at the BNN Rehabilitation Loka Batam, as well as explaining the role of BNN in making effective rehabilitation of narcotics addicts in general and specifically at the BNN Rehabilitation Loka Batam. This type of legal research is normative-empirical (applied law research), using a conceptual approach by analyzing theories related to criminal law specifically related to the main problem of research. The results of the study concluded the need for further study of the resident selection system. In this case the assessment process needs to do a more selective analysis in sorting resident candidates not only based on social support strata, but also paying attention to the severity of the resident so that the rehabilitation process can run more effectively. Then there needs to be a comprehensive academic study regarding rehabilitation patterns that are deemed appropriate to the conditions of the resident and local wisdom or characteristics of the people in Indonesia. The implementation of medical and social rehabilitation should be aligned with the conditions and characteristics of the Indonesian people. The substance of the program should be adjusted to the values adopted by the Indonesian people by balancing material on health, religion and society, improving the quality of medical and social personnel (counselors), and monitoring and evaluating the program needs to be done regularly so that socialization of the introduction of the program and its implementation can run systematically and consistently.